Indocyanine Green Mediated Photothrombosis (IMP) with Intravitreal Bevacizumab (IVB) for Treatment of Choroidal Neovascular Membrane (CNV) due to ARMD - Anisha Seth; Bhanu Pangtey; Neha Goel; Basudeb Ghosh (Delhi Journal of Ophthalmology)
Purpose: Choroidal neovascular membrane (CNV) is one of the leading causes of blindness among elderly patients. Anti-Vascular endothelial growth factors (VEGF) and photodyanamic therapy (PDT) are the only treatment options available for subfoveal and Juxtafoveal CNVM but are extremely costly. Indocyanine Green Mediated Photothrombosis (IMP) has been successfully used for subfoveal CNV due to ARMD and is much cheaper than PDT. Our study aims to evaluate IMP followed by intravitreal Bevacizumab in subfoveal and Juxtafoveal CNV due to ARMD. Methods: This prospective interventional study consisted of 15 eyes with subfoveal and juxtafoveal CNV due to ARMD. IMP was performed with low power diode laser augmented with indocyanine green dye (ICG) and followed 24 hours later with intravitreal bevacizumab 1.25 mg/0.05ml. Subjects were followed up at 6 weeks, 12 weeks and 16 weeks for BCVA, IOР, lens status assessment on slit lamp, fundus examination, FFA and SD-OCT. Results: Mean visual acuity improved from 0.136 preoperatively to 0.177 at 6 weeks, to 0.183 at 12 weeks and 0.185 at 16 weeks. Mean pre-treatment mean macular thickness (MMT) varied from 284.1 µт to 261.2 µт at 4 weeks post-treatment, to 268.8 µт at 12 weeks and to 267 µт at 16 weeks post-treatment. 10 eyes showed stabilization of vision with treatment till 16 week post treatment. Five eyes showed improvement in vision which was sustained till 16th week post treatment. No eye showed decrease in vision by the end of follow up. The difference was statistically significant at all visits. Conclusion: IMP in combination with intravitreal Bevacizumab is an effective treatment modality for CNV in ARMD.